Factors Associated With Components of Arterial Pressure Among Older Individuals (the Multinational MEDIS Study): The Role of the Mediterranean Diet and Alcohol Consumption. Issue 9 (24th July 2014) - Tyrovolas, Stefanos; Haro, Josep Maria; Polychronopoulos, Evangelos; Mariolis, Anargiros; Piscopo, Suzanne; Valacchi, Giuseppe; Makri, Kornilia; Zeimbekis, Akis; Tyrovola, Dimitra; Bountziouka, Vassiliki; Gotsis, Efthimios; Metallinos, George; et al.
<x xml:space="preserve">Abstract</x> The aim of this work was to evaluate factors associated with arterial blood pressure in a sample of older Mediterranean people without known cardiovascular disease. During 2005 to 2011, 2813 older (aged 65–100 years) individuals from 22 Mediterranean islands and the rural Mani region (Peloponnesus) voluntarily enrolled. Standard procedures were used to determine arterial BP and pulse pressure and for the evaluation of dietary habits (including tea and alcoholic beverages consumption), lifestyle, and anthropometric and clinical characteristics of the participants. Participants who reported low alcohol consumption (ie, 0–1 glasses per day) were less likely to have hypertension (odds ratio, 0.34; 95% confidence interval, 0.14–0.84) as compared with those who reported high alcohol consumption (ie, 5+ glasses per day). Adherence to the Mediterranean diet was inversely associated with mean arterial pressure (β coefficient, −0.18; 95% confidence interval, −0.33 to −0.16). Alcohol drinking remains an important modifiable risk factor for hypertension. Adherence to the Mediterranean diet was associated with decreased arterial peripheral resistance.